The right-wing also laughs. Graphic humor in the magazine El Caudillo de la Tercera Posición (Tempo e Argumento, 2016)
This paper presents a study of graphic humor in the Peronist magazine El Caudillo de la Tercera Posición. This magazine was published between 1973 and 1975 as a weekly political news publication and it became a flagship vehicle of the right-wing Peronism. It fought and denounced the ‘infiltration’ of the left-wing. Since the early issues it included a continuous humor section with caricatures and comic strips. By analyzing the humor section, it is possible to grasp the political culture of the Peronist right-wing and the stereotypes that it has built about its enemies. Keywords: Humor; Right-wing; Anticommunism; Peronism.